Education "Stop Bullying in Children" at SMP Negeri 45 Makassar - Nour Sriyanah; Suradi Efendi; Nofianti; Fitriani (IJCS: International Journal of Community Service, 2022)
Bullying is behavior negative which results in a person in a state of discomfort/pain and occurs repeatedly. The tremendous impact of bullying will occur on the victim and the perpetrator. The perpetrator will have a strong character while the victim of bullying will feel anxious. In fact, the most common problems are acts of violence that are carried out intentionally by individuals or groups of people with the aim of to hurt weaker victims. The purpose of this community service is that children are expected to be able to know what bullying is and apply stop bullying to children. The method in this service is the lecture method and the practice of bullying cases that usually occur in schools . The target of this service is 25 children. The results of this community service found that children who were given education would implement stop bullying because they already understood the impact it had on victims of bullying. The conclusion is that the community service carried out was successful.